Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Certainly! Let's solve the system of equations using the substitution method. The given system of equations is:
[tex]\[ \begin{cases} 3x + 4y = 9 \\ y = 2 - x \end{cases} \][/tex]
First, we'll substitute the second equation, [tex]\( y = 2 - x \)[/tex], into the first equation.
1. Substitute [tex]\( y = 2 - x \)[/tex] into [tex]\( 3x + 4y = 9 \)[/tex]:
[tex]\[ 3x + 4(2 - x) = 9 \][/tex]
2. Distribute the 4 in the equation:
[tex]\[ 3x + 8 - 4x = 9 \][/tex]
3. Combine like terms:
[tex]\[ 3x - 4x + 8 = 9 \\ -x + 8 = 9 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ -x = 9 - 8 \\ -x = 1 \\ x = -1 \][/tex]
Now that we have [tex]\( x = -1 \)[/tex], we substitute this value back into the second equation to find [tex]\( y \)[/tex]:
5. Substitute [tex]\( x = -1 \)[/tex] into [tex]\( y = 2 - x \)[/tex]:
[tex]\[ y = 2 - (-1) \\ y = 2 + 1 \\ y = 3 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y) = (-1, 3) \][/tex]
[tex]\[ \begin{cases} 3x + 4y = 9 \\ y = 2 - x \end{cases} \][/tex]
First, we'll substitute the second equation, [tex]\( y = 2 - x \)[/tex], into the first equation.
1. Substitute [tex]\( y = 2 - x \)[/tex] into [tex]\( 3x + 4y = 9 \)[/tex]:
[tex]\[ 3x + 4(2 - x) = 9 \][/tex]
2. Distribute the 4 in the equation:
[tex]\[ 3x + 8 - 4x = 9 \][/tex]
3. Combine like terms:
[tex]\[ 3x - 4x + 8 = 9 \\ -x + 8 = 9 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ -x = 9 - 8 \\ -x = 1 \\ x = -1 \][/tex]
Now that we have [tex]\( x = -1 \)[/tex], we substitute this value back into the second equation to find [tex]\( y \)[/tex]:
5. Substitute [tex]\( x = -1 \)[/tex] into [tex]\( y = 2 - x \)[/tex]:
[tex]\[ y = 2 - (-1) \\ y = 2 + 1 \\ y = 3 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y) = (-1, 3) \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.